The influence of particle size on the viscosity of water based ZnO nanofluid - Yalcin, Gokberk; Oztuna, Semiha; Dalkilic, Ahmet Selim; Wongwises, Somchai (ELSEVIER, 2023)
This experimental work investigated, the effect of ZnO particles' size on the water-based nanofluid viscosity. Nanofluid samples with 0.5, 0.75, and 1% volume concentrations were prepared using 20 and 50 similar to 150 nm ZnO nanoparticle sizes. Their viscosity was determined at 20, 30, 40, 50, and 60 similar to C. Scanning electron microscopy was employed to investigate the morphology of the nanoparticles. The maximum relative viscosity was measured for 1% ZnO (50 similar to 150 nm) as 1.35 times water. The stability of samples was evaluated for 1% ZnO (20 nm) and 1% ZnO (50 similar to 150 nm) by measuring their Zeta potential values which were similar to 21.4 mV and -23.1 mV, respectively. The correlation for the dynamic viscosity using measured data was compared with wellknown ones. The offered correlation has R-2 = 0.988, R-adj(2) = 0.987, and +/- 5.58% maximum deviation. The results showed that 12.8% reduction in viscosity is possible by varying nanoparticle sizes. The current study proposes additional new findings on the nanofluids' usability. (C) 2022 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University.
Keywords: Nanofluids; Viscosity; ZnO; Nanoparticle; Particle size; Stability; HEAT-TRANSFER CHARACTERISTICS; THERMAL-CONDUCTIVITY; ETHYLENE-GLYCOL; THERMOPHYSICAL PROPERTIES; HYBRID NANOFLUIDS; RHEOLOGICAL BEHAVIOR; DISPERSION BEHAVIOR; DYNAMIC VISCOSITY; TEMPERATURE; TIO2; Engineering